Active Learning Strategy on Higher Education Biology Learning: A Systematic Review - Pratiwi, Essy Dian; Masykuri, Mohammad; Ramli, Murni (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2021)
Student-centered learning intends to increase student participation. Biology subject is a broad scope and has a level of abstract concepts. Active learning has the potential to maximize the learning process of biology subjects. The purpose of the research is to describe the implementation and strategies of active learning applied to biology learning in higher education. The method used descriptive and systematic review. Selecting articles used the ERIC database. The search was carried out with predetermined categories, then a manual selection of the article to ensure the selected one. There are nine journals with nineteen articles analyzed at the higher education level of biology subject matter. This study's results, the implementation of active learning strategies, require support from lecturers and university stakeholders so that active learning runs effectively. An Active learning strategy used in biology material in higher education consists of the use of low-cost technology (virtual cell learning module) to high cost (SCALE-UP, clicker), low-cost learning without involving technology (card games, card organisms, kinesthetic physical models, 5E lesson plan, and pre-class reading guide) to outside the classroom (field training). The university's role and the understanding of lecturers in implementing active learning strategies have a crucial role in determining student learning outcomes. Lecturers and university stakeholders need to build cooperation, including a learning policy system and classroom implementation.